Systematic approach to sustainable urban development: reviewing challenges of informal settlements and peri-urban growth in sub-Sahara Africa - Temitope Olufolahan Olaniran; Thomas Terna Aule (Urban, Planning and Transport Research)
This paper systematically reviews scholarly literature on informal settlements in peri-urban areas, with a focus on the interplay of socio-economic, environmental, governance, and built environment factors contributing to their emergence and persistence. Drawing on 10 studies across predominantly sub-Saharan African contexts, the review analyses core variables, methodological designs, theoretical frameworks, and geographical patterns. Findings reveal that socio-economic exclusion, weak institutional coordination, and dual land governance systems significantly drive informality. Customary and religious institutions often mediate land access and conflict resolution, compensating for gaps in statutory urban planning systems. Environmental risks such as poor sanitation, contaminated water sources, and inadequate waste management remain under-addressed. Notably, the review identifies a critical gap in existing research: the limited application of architectural, spatial planning, and design-based strategies for upgrading and integrating informal settlements into the formal urban fabric. Although incremental upgrading has been proposed as a viable intervention, few studies offer context-sensitive, design-led frameworks for implementation. This study calls for interdisciplinary, solution-oriented approaches that blend policy, governance, and architectural insights to ensure inclusive, sustainable urban development. Recommendations emphasise participatory upgrading, improved service delivery, and legal recognition of informal settlements. The findings are relevant for policymakers, planners, designers, and researchers committed to addressing urban informality in sub-Sahara Africa and beyond.